Appropriateness of empiric therapy in patients with suspected Clostridium difficile infection. (4th June 2013) - Saade, Elie; Deshpande, Abhishek; Kundrapu, Sirisha; Sunkesula, Venkata C.K.; Guerrero, Dubert M.; Jury, Lucy A.; Donskey, Curtis J.
Abstract: Objective: The objective of this study was to test the hypothesis that many patients with suspected Clostridium difficile infection (CDI) receive inappropriate empiric therapy and/or receive continued therapy despite negative test results. Methods: We performed a 3 month prospective cohort study at the Cleveland Veteran Affairs Medical Center to assess the appropriateness of empiric CDI therapy for all patients with stool samples submitted for CDI testing. Empiric therapy for CDI was considered appropriate if patients with suspected CDI had findings suggestive of severe or complicated illness. Results: Of 251 patients tested for CDI, 53 (21%) received empiric treatment, including 45 (85%) treated with metronidazole and 8 (15%) treated with vancomycin. Of the 53 empirical therapy regimens, only 20 (38%) were deemed appropriate based on criteria for severe or severe, complicated CDI and 39 (74%) had negative laboratory testing for CDI. Twenty-one of 39 (54%) patients with negative testing were continued on therapy for three or more days despite the negative results. The key limitations of the study are the fact that it was conducted in a single institution and had a small sample size. Conclusion: In our facility, empiric treatment for CDI was common and more than half of empirical treatment was deemed inappropriate because patients did not meet criteria for severe CDI. Because CDI therapy may be associated with adverse effects, there is a need for interventions to improve the appropriateness of empiric CDI treatment.